Institutional barriers to the development and construction of urban hospitals - Hossein Ayoubi Najaf Abadi; Navid Fatehi Rad; Sanjar Salajegheh; Mohammad Jalal Kamali (Shahid Beheshti University of Medical Sciences, 2023)
Background: Increasing urban population and the need for accountability and citizen orientation have led decision makers to use the desired methods in the area of urban management. This article identified the barriers to development and construction of hospitals in metropolitan of Isfahan. Methods: This study was descriptive-correlational in terms of method. 376 people were studied. They were selected using stratified random sampling method. To data collection, a researcher-made questionnaire was used. It included 41 questions in two dimensions of urban and regional barriers and planning and management. The construct validity of the research variable structure was confirmed by exploratory factor analysis. Cronbach's alpha coefficient was also estimated to be higher than 0.7. Data analysis was performed using confirmatory factor analysis in AMOS-23.  Results: The indicators shown that the model for measuring institutional obstacles to achieve good urban governance is suitable. The results showed that planning and management and urban and regional variables as institutional barriers have a significant impact on the construction of the hospital and it shows that these structures have a direct impact on these barriers. Therefore, it can be said that the influence of planning and management variables was more than other dimensions. Conclusion: Based on the observations can be shown that the policy makers should identify the obstacles facing the collaborative models and then provide a suitable platform for their organizations. In order to reduce planning and management obstacles, should be managed within the framework of plans and stakeholders should be involved in the decision-making process.